Empowering public spaces as catalysers of social interactions in urban communities - Stauskis, Gintaras; Eckardt, Frank (Journal of Architecture and Urbanism, 2011)
Improving public spaces is a strategy of great importance for the successful future of our cities and their communities. The potential of places for citizen communication is often underestimated as stimulus for growth and development of urban communities and therefore public spaces are underused. The article analyses socioeconomic and psychological effects of architectural arrangement of traditional public spaces in modern perspective as areas for social interaction between different neighbourhood and citizen groups in an urban community, based on case examples of two cities: Vilnius in Lithuania and Weimar in Germany. Analysis of changing spatial composition and principles of social functioning are directly dependent on socio-political system of each different historical period and represent the chronological evolution of the present architectural appearance of the presented urban squares. The importance of local urban territorial communities is underlined in the article as they are the most important social entities for identifying the needs of local residents and in many cases are ready to take over the responsibility for rearrangement of the public spaces adjacent to their areas of residence. Based on a careful observation of public activities on going in the analysed urban squares in Vilnius and in Weimar, the principles of planning, functionality and spatial arrangement are analysed in the aspect of facilitation of social interactions on going or potentially possible in these spaces. The research identifies planning and spatial arrangement models that could facilitate the preferred ways of social interactions and generate the better overall aesthetical and functional quality of those places.Miesto viešosios erdvės kaip socialinio bendradarbiavimo vietos bendruomenėse katalizatoriusSantrauka. Viešųjų erdvių kokybės gerinimas yra svarbus miesto socialinės raidos uždavinys. Neįvertinus didelio viešųjų erdvių potencialo miesto bendruomenėms augti ir plėtotis, dažnai viešosios erdvės miestuose yra apleistos ir neišnaudotos, kartais jos užstatomos pastatais ir išnyksta. Pasiremiant dviejų miestų – Vilniaus Lietuvoje ir Veimaro Vokietijoje – pavyzdžiais, straipsnyje analizuojami socialiniai, ekonominiai ir psichologiniai miesto viešųjų erdvių architektūrinės struktūros efektai jų poveikio įvairių mieto gyventojų grupių bendravimui aspektu. Tiriamų miestų skverų ir aikščių erdvinė kompozicija ir jų socialinis reikšmingumas kito pagal besikeičiančius istorinių laikotarpių socialinius, politinius principus: tą parodo šių viešųjų erdvių architektūrinės planinės struktūros evoliucijos tyrimas. Straipsnyje iškeliamas vietos teritorinių bendruomenių kaip subjektų, tiesiogiai suinteresuotų greta jų gyvenamųjų vietų esančių viešųjų erdvių pertvarkymu, naudojimu ir priežiūra, vaidmuo. Remdamiesi atidžiu tiriamuose Veimaro ir Vilniaus skveruose ir aikštėse vykstančių viešojo bendravimo procesų stebėjimu, straipsnio autoriai pateikia rekomendacijas, kaip įvertinant miestiečių bendravimo specifiką reiktų tobulinti miestų viešųjų erdvių suplanavimą, erdvinę struktūrą, funkcionalumą ir kitus svarbius jų įrengimo aspektus.Reikšminiai žodžiai: urbanistinis projektavimas, kraštovaizdžio architektūra, viešoji erdvė, socialinis bendradarbiavimas, darnus mobilumas, prieinamumas.First Publish Online: 22 May 2013